Validating reusability of software projects using object-oriented design metrics - Ani, Z.C. (Springer Verlag, 2015)
Reusability is the highest priority that needs to be considered before developing good software projects. Without reusability, software projects would be hard to maintain or extend. In order to ensure the minimum reusability levels of quality attribute is achieved in designing software project, two versions of jUnit which were developed by software professionals have been assessed by using Quality Model for Object-oriented Design (QMOOD). Even though the obtained result showed that the design of jUnit projects achieved the standard, the result was still not validated by other object-oriented design metrics framework. Therefore, this paper will validate the design reusability of jUnit using CK Metrics. The result showed that jUnit has a good quality design and the reusability level can be used as a benchmark for designing other software projects. Â© Springer-Verlag Berlin Heidelberg 2015.